Exploring health-care providers' experiences in the care of clients on opioid agonist treatment in two western Canadian clinics. Issue 1 (March 2020) - Maina, Geoffrey; Tahir, Hira; Docabo, Angelica; Kahia, Nyambura; Brunelle, Caroline
Introduction: Prescribing methadone as part of opioid agonist therapy is a common treatment approach to manage opioid use disorder. Unfortunately, many clients prematurely discontinue opioid agonist therapy because of restrictions attached to the therapy. Purpose: The purpose of this study was to explore health-care provider experiences as they worked with clients on opioid agonist therapy in a western Canadian city. Methods: In this descriptive, qualitative study, we interviewed 18 health-care providers working in an opioid agonist therapy setting. The focus of the interviews was on the organization of opioid agonist therapy care at their clinic, their personal experiences and challenges faced when providing care to their clients. Interviews were recorded electronically and transcribed verbatim and thematic analysis was completed using NVIVO software. Results: The following three themes emerged from the data relate to the care organization and health care provider (HCP)-clients dynamics. These are: (1) fragmentation of care for a complex problem, (2) enforcing compliance to treatment, and (3) the importance of a therapeutic alliance to improve overall care. Conclusion: The opioid agonist therapy model is biocentric and emphasizes abstinence which can create tension between providers and clients. Making the model of care more patient centred might help to improve client retention rates and successful treatment outcomes.